Navigating Turbulence: Analyzing the Crisis Response of Sriwijaya Air following the SJ182 Plane Crash using Situational Crisis Communication Theory (SCCT) - Rahmawati, Annisa; Pratiwi, Miftha; Yusa, Muchammad Yustian (CHANNEL: Jurnal Komunikasi, 2024)
Aircraft accidents show that the industry is vulnerable to crisis and capture the complexity of crisis management and communication. This study examines the crisis response strategies employed by Sriwijaya Air in the aftermath of the SJ-182 plane crash on January 9, 2021. Utilizing the Situational Crisis Communication Theory (SCCT) framework, the research categorizes and analyzes the airline's crisis communication actions based on primary and secondary strategies. The content analysis of news articles from Kompas.com, Detik.com, CNN Indonesia, and Reuters, as well as posts from Sriwijaya Air's social media accounts, reveals the implementation of excuse, compensation, partial apology, and ingratiation strategies. The findings indicate that while Sriwijaya Air avoided denial strategies, its delayed response negatively impacted public perception. The study highlights the importance of prompt and transparent communication in crisis management. It suggests areas for future research, including examining internal decision-making processes and the long-term impacts on organizational reputation and resilience.